PENDIDIKAN HUMANIORA DALAM AL-QUR’AN - Anwar, Bakri (Universitas Islam Negeri Alauddin Makassar, 2021)
Education is a problem that always preoccupies the minds of thinkers and lovers of goodness. In this field, the writers and discussants also try to give the meaning of education, even though their views differ about the limits of the meaning of education and its goals, but all agree on the importance of education for humans in order to live happily and achieve a high level of happiness in the world and the hereafter.If the above education is considered important for every human being. So humanities education is also more important for a nation, with humanities education they can maintain their morals, and can make their lives happy. In this modern era, humanities education is very important for humans, because this era is the era of technological development, development and science. Therefore, Islamic education plays an important role in shaping and developing the potential of the whole human being, so that it is able to carry out the mandate and responsibilities as a caliph on earth, and is able to implement everything that Allah has asked for. Besides, Islamic education aims to develop human potential both in terms of reason, spirituality and morals. In order to get to the goal, the writer uses descriptive and inductive methods, namely a method that originates from specific facts and ends with general conclusions. With this method leads to definitions, principles and general essence. Besides that, in this discussion the writer also uses deductive methods and documentary methods. From the results of the above research shows that Islamic education is the principle of humanities education, in this case there are several things: First, improving the standard of human life in terms of science and culture: Second, forming a spirit of piety to Allah SWT. Third, forming human potential as perfect as possible. Fourth, creating monotheism in them. Fifth, Directing to carry out God's mandate on earth. The conclusion of this study is that Islamic education and humanities is an increase in the quality of devotion to Allah, so as to achieve happiness in the world and the hereafter. The suggestions related to the above research are expected to further researchers to expand and deepen this research, especially Islamic education and humanities.